HUBUNGAN KOMUNIKASI KEPALA SEKOLAH DENGAN KINERJA GURU TK SE KECAMATAN TAMPAN KOTA PEKANBARU - Maulina, Melisa; Wilson, Wilson; Febrialismanto, Febrialismanto (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2014)
Abstract: This research aims to find out the relationship of headmaster communications with performance of kindergarten teacher in Tampan sub district Pekanbaru City. This research is a quantitative study by using correlation techniques. This variable in of this research consisted of two variable that is headmaster communications and performance of kindergarten teacher. The sample were used in this research is 73 people. The data collection techniques used were through questionnaires in the form of Likert scale. Data were analyzed to test and validity of reliability using large-scale trials and analysis of statistical methods with SPSS for windows ver.16. In this research the hypothesis is that a relationship of headmaster communication with performance of kindergarten teacher in the sub district of Tampan Pekanbaru city. The result showed a positive and significant relationship between headmaster communications with performance of kindergarten teacher in the sub district Of Tampan Pekanbaru city. It can be found from the analysis of data obtained is the value of rcount at 0,255 while rtable ( 5%) (dk = n - 2 = 73 - 2 = 71) so that rtable = 0,235. Because the value of rcount is greater than the value of rstandar or 0,255> 0,235. It can be concluded that there is a positive and significant relationship between the variable of headmaster comunication with performance of kindergarten teacher. The result of determinant coefficient is r2 = 0,065 with p = 0,029 ( p < 0,05) so, it can be seen that headmaster communications give influence equal to 6,5% to performance of kindergarten teacher.Keyword: headmaster comunications, performance of kindergarten teacher.